Peningkatan Literasi Membaca dan Menulis Pada Siswa Melalui Media Pembelajaran Alat Peraga Flashcard Alphabet di SDN Balonggemek 2 Megaluh 2023-2024 - Sutrisno, Sutrisno; Fahmi, Moh. Ifan; Abidin, Hasan; Sholich, Moh. (LPPM Institut Agama Islam Bani Fattah Jombang, 2024)
Reading and writing literacy are essential basic skills that everyone must master. These literacies are needed to access information, communicate, and develop oneself. For elementary school students, reading and writing literacy are critical skills to be acquired. Good reading and writing literacy will help students understand lessons, complete school assignments, and develop creativity. The use of alphabet flashcards in teaching reading and writing is an effective method to assist students in developing their literacy skills. However, it is important to remember that such teaching aids should be used as part of a broader and integrated learning approach that includes teacher-student interactions, appropriate reading materials, and individual support for students who need additional assistance. This community service program employs a student-centered learning strategy. This strategy emphasizes the role of students as active participants in the learning process, encouraging them to construct their own knowledge.